2009
DOI: 10.5688/aj730235
|View full text |Cite
|
Sign up to set email alerts
|

Improvisational Exercises to Improve Pharmacy Students' Professional Communication Skills

Abstract: Objective. To create and implement improvisational exercises to improve first-year pharmacy students' communication skills. Design. Twelve 1-hour improvisational sessions were developed and added to an existing/established patient communication course to improve 3 basic skills: listening, observing and responding. Standardized patient examinations were used to evaluate student communication skills, and course evaluations and reflective journaling were used to evaluate students' perceptions of the improvisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 5 publications
1
36
0
Order By: Relevance
“…However, many of the activities described are fragments of larger communication courses and curriculum, and typically involve (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) 4 (13,14,20,22) 1 (11) 2 (13,23) 1 (21) 4 (12,16,20,24) 2 (18,20) 0 InterD 5 (13,14,20,23,26) 6 (13,14,20,(26)(27)(28) 1 (28) 3 (13,23,29) 1 (29) 3 (20,23,26) 1 (28) 0 Seminar 4 (11,13,14,30) 3 (11,13,...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, many of the activities described are fragments of larger communication courses and curriculum, and typically involve (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) 4 (13,14,20,22) 1 (11) 2 (13,23) 1 (21) 4 (12,16,20,24) 2 (18,20) 0 InterD 5 (13,14,20,23,26) 6 (13,14,20,(26)(27)(28) 1 (28) 3 (13,23,29) 1 (29) 3 (20,23,26) 1 (28) 0 Seminar 4 (11,13,14,30) 3 (11,13,...…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies involved interdisciplinary activities or seminars that combined pharmacy students with other health professions students, or simulation activities of common interprofessional interactions. One study involved writing a script modeling different communication styles used when talking to a physician over the phone, 39 another involved acting out a conversation with fellow students using improvisation to improve interprofessional conversational skills, 11 while others involved engaging in telephone communication with an actual prescriber. 22,35,50 General interpersonal communications skills are those not directed at a specific type of interaction, but which can be used in all forms of conversation.…”
Section: Description and Categorization Of Communication Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…To answer these questions, so conducting the research was needed under the title: "The Effect of Improvisation Technique towards Students" Speaking Ability at Class XI of Senior High School 12 Padang" This research was significant to conduct based on benefits: (1) Teacher is more creative in choosing the strategies and techniques in teaching process; (2) Teacher can demonstrate the usefulness of exercises once or twice in the beginning to build rapport and trust with the students, and (3) Students of all levels are able to practice the language immediately in learning the material. Boesen, Herrier, Apgar, & Jackowski (2009) indicated that pharmacy students felt that the improvisation sessions had a positive impact on their overall communication skills. Using improvisation training to improve pharmacy students" communication skills should be considered and could be readily implemented in other colleges.…”
Section: Introductionmentioning
confidence: 99%